A 4-year follow-up of the need for orthodontic treatment using the Dental Aesthetic Index-DAI: an exploratory analysis - Silvia Amelia Scudeler VEDOVELLO; Ana Letícia Mello de CARVALHO; Diego Patrik Alves CARNEIRO; Marcelo de Castro MENEGHIM (Brazilian Oral Research)
Abstract This study aim was to evaluate the need for orthodontic treatment of mixed to permanent dentition using the Dental Aesthetic Index (DAI) in a 4-year follow-up. A longitudinal study was conducted with 353 children in the stages from mixed (T1) to permanent (T2) dentition. The need for orthodontic treatment was assessed using the DAI categorized into: DAI 1 (absence of malocclusion and orthodontic treatment need; DAI ≤ 25); DAI 2 (malocclusion is defined and elective orthodontic treatment is needed; DAI = 26 to 30); DAI 3 (severe malocclusion and a desirable orthodontic treatment need; DAI = 31 to 35) and DAI 4 (severe malocclusion and a mandatory orthodontic treatment need; DAI ≥ 36). The Bowker symmetry test was used to determine agreement in the categorization of DAI at T1 and T2, with a significance level of 5%. The results showed a significant disagreement in the need for orthodontic treatment between T1 and T2 (p<0.05). In 34.6% of children evaluated in T1, the same need for orthodontic treatment was maintained in T2. According to the DAI, in 60.8% of the children, the need decreased, and in 39.2% their need for orthodontic treatment increased. This preliminary longitudinal study using DAI, showed a decrease in malocclusion and need for orthodontic treatment as the dentition transitioned from mixed to permanent occurred. This finding has valuable implications for epidemiological data in orthodontics.